2004
DOI: 10.1007/s10805-004-4306-z
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Ethical Behaviour among Business Faculty in Canada

Abstract: Faculty members at Canadian business schools were surveyed regarding their ethical perceptions of behaviours related to undergraduate instruction. Fifty-five behavioural statements were listed and respondents were asked to rate the extent to which they felt each behaviour was ethical or unethical. The only item that respondents endorsed as unequivocally unethical (90% indicated it was "definitely unethical") was "Becoming sexually involved with an undergraduate in one of your classes." We also compared the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…Much of the existing research focusing on faculty and academic integrity examines relationships between students and faculty rather than faculty members" understanding or awareness of students" knowledge or attitudes regarding academic integrity issues (e.g., Laband & Piette, 2000;Mason, Beardon, & Davis Richardson, 1990;McKay, Kidwell, & Kling, 2007;Tabachnick, Keith-Spiegel, & Pope, 1991). For example, survey research has indicated that becoming sexually involved with a student, receiving sexual favors, money or gifts in exchange for grades, giving lower grades to students who strongly oppose your views, failure to acknowledge significant contributions from students in a publication, providing academic credit instead of financial remuneration for a student"s work, ignoring a colleague"s unethical behaviour, and including false or misleading information in a reference letter were all perceived to be unethical behaviours by faculty Laband & Piette, 2000;McKay et al, 2007;Robie & Keeping, 2004;Robie & Kidwell, 2003;Tabachnick et al, 1991). Personal infractions also constituted significant breaches of misconduct, for example, manipulating, fabricating, or otherwise falsifying lab data (Laband & Piette, 2000;McKay et al, 2007), and plagiarism (McKay et al, 2007).…”
mentioning
confidence: 99%
“…Much of the existing research focusing on faculty and academic integrity examines relationships between students and faculty rather than faculty members" understanding or awareness of students" knowledge or attitudes regarding academic integrity issues (e.g., Laband & Piette, 2000;Mason, Beardon, & Davis Richardson, 1990;McKay, Kidwell, & Kling, 2007;Tabachnick, Keith-Spiegel, & Pope, 1991). For example, survey research has indicated that becoming sexually involved with a student, receiving sexual favors, money or gifts in exchange for grades, giving lower grades to students who strongly oppose your views, failure to acknowledge significant contributions from students in a publication, providing academic credit instead of financial remuneration for a student"s work, ignoring a colleague"s unethical behaviour, and including false or misleading information in a reference letter were all perceived to be unethical behaviours by faculty Laband & Piette, 2000;McKay et al, 2007;Robie & Keeping, 2004;Robie & Kidwell, 2003;Tabachnick et al, 1991). Personal infractions also constituted significant breaches of misconduct, for example, manipulating, fabricating, or otherwise falsifying lab data (Laband & Piette, 2000;McKay et al, 2007), and plagiarism (McKay et al, 2007).…”
mentioning
confidence: 99%
“…The only behavior that was endorsed as unequivocally unethical was "becoming sexually involved with an undergraduate in one of your classes." When the results were compared to an American sample the general finding was that Canadian professors viewed more of the behaviors in question as less ethical than did their American counterparts (Robie and Keeping 2004).…”
Section: Literature Reviewmentioning
confidence: 94%
“…Both students and academics in different fields of social sciences experience ambiguity about which behaviors are morally acceptable (e.g., Holmes et al 1999;Robie and Kidwell 2003;Robie and Keeping 2005). Policy, however, and honor codes may impact on students' perceptions of problematic situations and their likelihood of reporting an academic integrity problem both in behavioral sciences (Rose and Fischer 1998) and in business subjects (McCabe et al 2006;Bryan et al 2009).…”
Section: Sociology and Social Workmentioning
confidence: 99%